Effect of natural and synthetic surface coatings on the toxicity of multiwalled carbon nanotubes toward green algae. (March 2015) - Zhang, Luqing; Lei, Cheng; Chen, Jiajun; Yang, Kun; Zhu, Lizhong; Lin, Daohui
Abstract: Ubiquitous dissolved organic matter (DOM) from various sources can interact with discharged multiwalled carbon nanotubes (MWCNTs) and pose distinct effects on the toxicity of MWCNTs to aquatic organisms. This study for the first time compared effects of a natural originated humic acid (HA) and two synthetic surfactants (sodium dodecylbenzenesulfonate – SDBS, octyl phenoxy polyethoxyethanol – TX100) on the toxicity of MWCNTs to a unicellular green alga ( Chlorella pyrenoidosa ). Algal growth inhibition, cell surface hydrophobicity, oxidative stress, MWCNT-cell agglomeration, and cell morphology change and internalization of MWCNTs were assayed to investigate individual and combined toxicities of MWCNTs and DOMs, and mechanisms underlying different effects of DOMs on the toxicity of MWCNTs were specifically addressed. It is shown that SDBS and TX100 were capable of promoting cell internalization of MWCNTs and triggering higher oxidative stress, and thereby increasing the toxicity of MWCNTs; while HA could alleviate the toxicity of MWCNTs through limiting cell internalization of MWCNTs and reducing oxidative stress. The outcomes of this work shed new light on the assessment of ecological toxicity of discharged nanomaterials.